Demokrasi Menundukkan Anarki - Said Akbar, Andi Ali (Political Science Program, Universitas Negeri Semarang, 2016)
Freedom and political competition in the Indonesian democracy are vulnerable to the practices of antagonistic politics. It can be seen from the growing of violence acts as the struggle method of some mass organizations, whether those with the religious identity or those with the political identity. The triggering point can be from the reactionary response on the incapability of accepting the consequence of living for democracy prior to the context of implementing the tolerant and pluralist ethics.The rise of minority group reputation in the political arena, the policies that are not in favor of the majorityand the tolerance towards the other religious/belief groups are included in the list of issues which are vulnerable to the violence acts. In addition, the problem can also come from the ineffectiveness of the state in establishing the law and tranquility. In this case, the people use their own logic of power to substitute the failure of the state. Unfortunately, the state seems to ignore various diseases of social demoralization. The efficacious cure to organize social organizations is that the government shall release the mass organization law. However, the state undergoes the uneasy dilemma. The activists of civil society keep on guard against the state in order not to deeply intervene the civil public space. Therefore, the state and the society have to respect the constitution and make the democratic value as a tradition in the intern of mass organization. Then, the ethics is made as the basic for anticipating various social problems. Besides, the state has to be effective in establishing the law and tranquility in the living of democracy. So, the existence of the mass organization law can be understood together as long as the instrumental effectivity creates peace in the state.